Transparent Government and Business Regulation : "Open for Business?" - Geginat, Carolin (World Bank, Washington, DC, 2014)
This paper presents new indicators for 185 economies measuring the accessibility of business regulatory information. The paper shows that the new data can serve as meaningful proxies for the overall transparency of governments and the new data have explanatory power for the quality of business regulation. The paper finds the regulatory environment to be most opaque in Sub-Saharan Africa and the Middle East and North Africa, where businesses can often only access basic regulatory information by meeting a government official. By contrast, in countries in the Organisation for Economic Co-operation and Development and Eastern Europe and Central Asia, access is more direct via websites, public billboards, and brochures. Moreover, Organisation for Economic Co-operation and Development economies are more consistent in their transparency efforts across government agencies. The paper also finds that while resources as proxied by income levels play some role in explaining why some economies make more information easily accessible than others, those resources are not the only determining factor; regardless of income, more democratic governments tend to make greater transparency efforts. Finally, easier access to basic regulatory information is associated with greater regulatory quality and less corruption.